From authority religion to spirit religion an intellectual biography of George Burman Foster, 1857-1918 - Peden, Creighton, 1935- (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
George Burman Foster (1857-1918) was a key figure among the philosophers and theologians who composed the early ""Chicago School."" This volume makes available the development of Foster's religious thought by exploring his major writings as well as diverse shorter works. Conclusions are provided following each major section of the book. Through this approach we discover that Foster was laying the foundation for the emergence of American humanism.
Table of contents; preface; historical sketch; the finality of the christian religion; the function of religion in man's struggle of existence; heresy trial; christianity in its modern expression; friedrich nietzsche; selection of diverse shorter writings of g. b. foster; summation; notes; bibliography; index.
Description based on print version record.
Keywords: Foster, George Burman, -- 1858-1918.; Theologians -- Illinois -- Chicago; Chicago school of theology; Humanism, Religious; Religious thought; RELIGION / Agnosticism; Electronic books